Dynamics of Spatial Transformation in Pekanbaru City During the Era of Regional Autonomy - Wahyu Hidayat (International Journal of Architecture and Urbanism, 2024)
Pekanbaru City in its development has gone through a number of periods of power in a span of more than two hundred years. The era of regional autonomy gave more authority to the regions to develop their cities. Stable economic growth has made Pekanbaru City one of the urbanization destinations in the Sumatra region. These two things make the morphology of Pekanbaru City has dynamically transformed into a metropolitan city. This study found that the city grows and develops no longer oriented to the city center, but has spread evenly to all parts of the city area. The road structure system is also no longer dependent on the main road around the city center, but has reached all other parts of the city. Urban transformation is still dynamic based on city government regulations and market forces.